Mechanical properties of biocomposite from polylactic acid and natural fiber and its application: A Review study - Mochamad Asrofi; Revvan Rifada Pradiza; Muhammad Yusuf; Midhun Dominic C. D.; R. A. Ilyas (Universitas Muhammadiyah Magelang, 2025)
In the past decade, the development of biocomposite materials has attracted much attention due to the growing concerns about petroleum-based natural resource depletion and pollution. Among the various biocomposite materials, polylactic acid (PLA) is one of the most widely produced and ideal for use in commercial products. The manufacture of PLA biocomposites with natural fiber reinforcement as an alternative material that replaces synthetic materials is widely researched. The different types of natural fiber sources used in the incorporation of matrix and fibers are very important as they affect the mechanical properties of the biocomposites. In addition, PLA-based biocomposites can be produced by a wide variety of methods that can be found in various commercializations. This study aims to present the recent developments and studies carried out on the development of PLA-based natural fiber biocomposites over the past few years. This study discusses PLA biocomposite research related to their potential, mechanical properties, some manufacturing processes, applications, challenges, and prospects.